Lebanon Reform, Recovery, and Reconstruction Framework - World Bank Group; United Nations; European Union (World Bank, Washington, DC, 2020)
The framework for reform, recovery, and reconstruction (the 3RF) is part of a comprehensive response to the massive explosion on the Port of Beirut on August 4, 2020. It is a people-centered recovery and reconstruction framework focusing on a period of 18 months that will bridge the immediate humanitarian response and the medium-term recovery and reconstruction efforts to put Lebanon on a path of sustainable development. The overall objective of the 3RF is to help address the urgent needs of the affected population and ensure that results are delivered through an efficient, timely, and well-coordinated recovery and reconstruction effort, with the involvement of all stakeholders and support from the international community. The 3RF is structured around four strategic pillars: (1) improving governance and accountability; (2) jobs and opportunities; (3) social protection, inclusion, and culture; and (4) improving services and infrastructure. Each pillar identifies a set of strategic objectives and priority areas across both the recovery track and the reform and reconstruction track. The 3RF is also designed to contribute to: (a) consensus-building among the government of Lebanon and Lebanese non-state actors on the required enabling policy environment and on priorities for recovery and reconstruction; (b) an agreed reconstruction and recovery framework between Lebanese society and development partners; (c) a programmatic and integrated approach across all sectors; (d) harmonized financing that aligns with the framework; and (e) a gradual transition from humanitarian response to recovery and reconstruction. The report is organized as follows: section one gives context and key challenges; section two presents 3RF scope and strategic objectives; section three presents macroeconomic stabilization as a foundation for recovery and reconstruction; section four discusses the 3RF pillars; section five gives institutional and monitoring arrangements; and section six presents 3RF financing strategy.